The current state and prospects of China’s environmental, social, and governance policies - Ju, Binbin; Shi, Xiaonan; Mei, Yueru (Frontiers in Environmental Science, 2022)
In recent years, climate change is getting more and more attention all around the world. China is a major participant in global climate governance. Enterprises play an important role in climate change governance, and the development of ESG concept is highly unified with the realization of global climate change governance and the “peaking carbon emission and carbon neutrality” goal in China. However, the development of ESG in China still faces many challenges. Based on the existing literature, data and policy documents, we analyze the current situation and existing problems of ESG development in China. Moreover, we propose ESG development policy recommendations that are suitable for China’s national conditions. Finally, in the context of environmental protection and resource conservation, our study will help enterprises achieve sustainable development.